2019
DOI: 10.1017/s0030605318001497
|View full text |Cite
|
Sign up to set email alerts
|

Conservation importance of previously undescribed abundance trends: increase in loggerhead turtle numbers nesting on an Atlantic island

Abstract: For many species abundance data from across their entire range are incomplete, and therefore it is difficult to accurately assess their conservation status. Even for species that are large, charismatic and relatively easy to study, conservation assessments are often hampered by lack of data. Here we report a marked, previously undescribed, increase in numbers at a breeding colony of the loggerhead turtle Caretta caretta, a species that is Critically Endangered in several parts of its range, and place this repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Around 65% of nests in this population are laid on the island of Boa Vista (Laloë et al, 2019; Figure 1).…”
Section: Study Areamentioning
confidence: 97%
See 1 more Smart Citation
“…Around 65% of nests in this population are laid on the island of Boa Vista (Laloë et al, 2019; Figure 1).…”
Section: Study Areamentioning
confidence: 97%
“…The study took place on the island of Boa Vista, Cabo Verde, West Africa, the world's second largest nesting aggregation of loggerhead sea turtles Caretta caretta (Laloë et al, 2019;Marco et al, 2012).…”
Section: Study Areamentioning
confidence: 99%
“…The increase in loggerhead turtle nesting numbers suggests that if threats to adult turtles are ameliorated, small populations can recover-and indeed, an absence of Allee effects has been noted in the Cayman Islands and in other nesting populations (Bell et al, 2010;Mazaris et al, 2017). A reduction of wild sea turtle harvesting is also thought to have played an important role in the increase in loggerhead turtle nest numbers in Cape Verde (Marco et al, 2012), which showed a 15-fold increase over a 10-year period (2008-2017) (Laloë et al, 2020). However, wider environmental factors also likely influence these trends; between 1999 and 2007, the same period where there was no increase in loggerhead nests in the Cayman Islands, growth rates of Northwest Atlantic loggerhead turtles declined significantly (Bjorndal et al, 2013).…”
Section: Loggerhead Population Trendmentioning
confidence: 99%
“…Recent data shows that this loggerhead subpopulation might be the largest population of this species worldwide [3,4]. Furthermore, after the Island of Boavista, the shores of the Island of Maio are, together with the Island of Sal, the most important nesting sites in the archipelago [5,6].…”
Section: Introductionmentioning
confidence: 99%